2020
DOI: 10.1136/bmjopen-2020-037070
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics associated with a poor response to non-surgical multidisciplinary management of knee osteoarthritis: a multisite prospective longitudinal study in an advanced practice physiotherapist-led tertiary service

Abstract: ObjectivesTo explore patient characteristics recorded at the initial consultation associated with a poor response to non-surgical multidisciplinary management of knee osteoarthritis (KOA) in tertiary care.DesignProspective multisite longitudinal study.SettingAdvanced practice physiotherapist-led multidisciplinary orthopaedic service within eight tertiary hospitals.Participants238 patients with KOA.Primary and secondary outcome measuresStandardised measures were recorded in all patients prior to them receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Effective working memory is necessary to make decisions, reason and plan, however is decreased in people with persistent pain (Berryman et al., 2013), potentially making accurate assessment of change more challenging than in non‐pain populations. Pre‐treatment expectations impact intervention outcomes in persistent pain conditions (Eklund et al., 2019; Hill et al., 2007; Lurie et al., 2016; O'Leary et al., 2020; Turner et al., 2002). Previous studies demonstrated 80% of people prioritised pain reduction as the most important outcome following pain treatment interventions (Casarett et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Effective working memory is necessary to make decisions, reason and plan, however is decreased in people with persistent pain (Berryman et al., 2013), potentially making accurate assessment of change more challenging than in non‐pain populations. Pre‐treatment expectations impact intervention outcomes in persistent pain conditions (Eklund et al., 2019; Hill et al., 2007; Lurie et al., 2016; O'Leary et al., 2020; Turner et al., 2002). Previous studies demonstrated 80% of people prioritised pain reduction as the most important outcome following pain treatment interventions (Casarett et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…After duplicates were removed, 6931 records were screened, and 151 full-text articles were reviewed ( Fig 1 ). 32 studies were included in the systematic review [ 10 , 12 , 14 18 , 21 , 24 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study evaluated the association between baseline kinematics and knee pain but did not report data for age, sex, BMI, comorbidities, depression and OA severity. Seven studies were considered multidisciplinary with tailored interventions by health professionals such as dieticians or occupational therapists [ 10 , 12 , 15 , 18 , 30 , 39 , 43 ]. Fifteen studies were described as an OAMP, including GLA:D ® [ 26 , 41 , 45 , 46 ], BOA [ 24 , 25 , 28 , 29 , 44 , 48 ], Osteoarthritis Chronic Care Program (OACCP) [ 10 , 12 , 43 ] and the Joint Clinic [ 15 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations